Continuity and change in the European Union's approach to enlargement: Turkey and Central and Eastern Europe compared - Icener, Erhan; Phinnemore, David; Papadimitriou, Dimitris (Routledge Journals, Taylor & Francis Ltd, 2010)
Existing studies of European Union (EU) enlargement provide few answers to questions concerning continuity and change in the dynamics of the process. This article identifies a number of conditioning factors that have shaped the EU's approach to eastern enlargement and traces elements of continuity and change in the EU's handling of Turkey's membership aspirations. The article focuses on three established factors - member state preferences, supranational activism and EU capacity - and two less prominent factors - public opinion and narrative frame.
Keywords: European Union; enlargement; Turkey; public opinion; narrative frame